Hubungan Pengetahuan Ibu Hamil Tentang Covid-19 Dengan Perilaku Pencegahan Covid-19 Di Wilayah Kerja Puskesmas Seginim Kabupaten Bengkulu Selatan - Nuryana, Agusnina; Rahmarianti, Gusni; Hayadi, Firman; Paskana, Kristina (Jurnal Kebidanan Manna, 2022)
The purpose of this study was to determine the relationship between knowledge of pregnant women about Covid-19 and Covid-19 prevention behavior in the working area of the Seginim Health Center, South Bengkulu Regency. This research is an analytic study with a cross sectional design. The population of this study were all pregnant women who were in the working area of the Seginim Health Center with a total sample of 76 people. Data analysis was performed by chi-square test. The results of the study were mostly with less knowledge, namely as many as 30 people (39.5%), most of the respondents with good covid-19 infection prevention behavior, namely 41 people (5.9%). The results of statistical tests using the chi-square test showed X2 count (23.079) > X2 table (5.591) and the value of (0.000)<ρ(0.05). There is a relationship between knowledge of pregnant women and COVID-19 prevention behavior in the work area of the Seginim Health Center, South Bengkulu Regency.